2011
DOI: 10.1111/j.1365-2265.2011.03985.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between anthropometrical measurements, body composition, single-nucleotide polymorphisms of the hypothalamus/pituitary/adrenal (HPA) axis and HPA axis functioning

Abstract: Our preliminary data show that in both men and women (18-55 years, BMI 19-41 kg/m(2) ), the SNP's BclI and C8246T of the HPA axis were primarily related to altered HPA axis functioning, rather than to altered anthropometric measurements and body composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…No SNPs in the FKBP5 gene were included in this initial candidate gene study. Further, although no SNPs in POMC gene were associated with HPA measures in our study, a small study in women found an association with the rs1042571 CC genotype in the POMC gene and higher cortisol levels [24]. This POMC SNP was not included in our study, but is in moderately high LD with rs934778 (R 2  = 0.59), which was not associated with any HPA measures directly in our study, but there was limited evidence of an interaction between this SNP and birthweight (p-value = 0.014).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…No SNPs in the FKBP5 gene were included in this initial candidate gene study. Further, although no SNPs in POMC gene were associated with HPA measures in our study, a small study in women found an association with the rs1042571 CC genotype in the POMC gene and higher cortisol levels [24]. This POMC SNP was not included in our study, but is in moderately high LD with rs934778 (R 2  = 0.59), which was not associated with any HPA measures directly in our study, but there was limited evidence of an interaction between this SNP and birthweight (p-value = 0.014).…”
Section: Discussioncontrasting
confidence: 90%
“…Cortisol concentrations have been evaluated most frequently and polymorphisms in genes including the FK506 binding protein ( FKBP5 ) [23], glucocorticoid receptor ( NR3C1 ) [24], mineralcorticoid receptor ( NR3C2 ) and pro-opiomelanocortin ( POMC ) [24] have been associated with cortisol levels in adults. Haplotypes of the glucocorticoid receptor have been found to modify the association between birth length and fasting plasma cortisol in older adults [25].…”
Section: Introductionmentioning
confidence: 99%
“…27 In addition, it has been shown that activation of the HPA axis is associated with visceral adiposity observed with a high WHR in women. 28 WHHR remained a significant predictor of CVD risk after adjustment for established risk factors in men and women in the cohort of 60-year-old men and women, whereas significance was only seen in men in the MDC-CC. This may be partly explained by the necessary age adjustments in the latter study, and may also explain why several measures were significant after adjustments for established CVD risk factors in men in the Stockholm cohort in contrast to findings from the Emerging Risk Factors Collaboration with pooled data from 58 cohorts.…”
Section: Potential Mechanismsmentioning
confidence: 83%
“…In addition, the intronic SNP rs6713532 was marginally associated with AD or CD in EAs, and SNP rs6719226 in the 5′ flanking region was associated with OD in AAs (Zhang et al 2009). In another study, SNP rs1042571 in the 3′ UTR was associated with higher cortisol exposure and reduced negative feedback of the HPA axis, in a nonchallenged condition, in women (Rutters et al 2011). …”
Section: The Proopiomelanocortin Gene (Pomc)mentioning
confidence: 95%